RANCANG BANGUN E-HEALTH TRACKER UNTUK DETEKSI DETAK JANTUNG, SATURASI OKSIGEN, SUHU TUBUH, DAN TEKANAN DARAH BERBASIS IoT - I Dewa Gede Agung Wahyu Mahendra; I Made Beni Satriya; I Gusti Agung Putu Raka Agung; Gede Sukadarmika (Program Studi Teknik Elektro UNUD, 2025)
The Internet of Things (IoT)-based health monitoring system presents a potential solution to improve remote healthcare services, particularly in areas with limited access. This study developed an IoT-based E-Health Tracker capable of measuring four vital health indicators: heart rate, oxygen saturation (SpO₂), body temperature, and blood pressure. The system integrates the MAX30102, DS18B20, and MPX5050GP sensors with Arduino Uno and ESP32 microcontrollers. Measurement data is displayed locally via an LCD TFT. Evaluation was carried out through experimental testing involving 5 participants over 7 consecutive days (a total of 35 samples). The system’s results were compared with conventional medical devices (oximeter, thermometer, and blood pressure monitor), and accuracy was assessed using the Mean Absolute Percentage Error (MAPE) method. The results showed that the system achieved very good to good accuracy levels, with MAPE values of 1.75% for heart rate, 1.28% for SpO₂, 2.67% for body temperature, and 7.74% for blood pressure. This system can serve as an alternative for IoT-based health monitoring.